Erratum: CARLOS PRIETO & GABRIEL RODRIGUEZ (2012) A new iridescent “elfin” butterfly species of Podanotum (Lepidoptera: Lycaenidae: Eumaeini) from the Colombian Andes. Zootaxa, 3303, 59–64. - Prieto, Carlos; Rodriguez, Gabriel (Zootaxa, 2012)
(Erratum)